The Contribution of the School Environment and the Competence of Islamic Education Teachers in the Formation of Morals of High School Students - Didit Darmawan; Irfan Nofa Sagita; Muhammad Syifa' Fairuz Zamzami (Lembaga Penelitian dan Pendidikan Mandala, 2026)
The problem of student morality at the senior high school level remains a challenge in educational practice, reflected in low discipline, reduced respect for teachers, and the emergence of aggressive behavior in the school environment. This phenomenon indicates that the construction of student morality is not only determined by the learning process in the classroom, but is also influenced by the condition of the school environment and the competence of teachers as role models. This study aims to analyze the contribution of the school environment and the competence of Islamic Religious Education teachers to the process of forming student morality. The study used a qualitative approach with a literature study design through a critical review of articles, scientific journals, and various relevant academic references. The results of the study indicate that a conducive, orderly, and religious school environment contributes to forming positive behavioral habits through a culture of discipline, religious activities, and harmonious social interactions. On the other hand, the personality competence of Islamic Religious Education teachers, especially in the aspects of exemplary behavior, moral integrity, and discipline, also makes an important contribution to the process of internalizing students' moral values. This finding confirms that the formation of students' morals requires synergy between a supportive school environment and mature teacher competence, so that character education strategies need to be developed holistically and sustainably.